Effect of recombinant divercin RV41, structural variants and the activators of potassium channels on Listeria monocytogenes EGDe - Rihakova, J; Prevost, H; Demnerova, K; Drider, D (Folia microbiologica, 2011)
The effect of recombinant divercin RV41 (DvnRV41) and its structural variants on the K-channel formation was determined. The growth of Listeria monocytogenes EGDe (sensitive phenotype) and its isogenic strain (resistant phenotype) was assessed in the presence of DvnRV41 combined or not with pinacidil, NS1619, cromakalim (as K-channel activators), iberiotoxin and glipizide (as K-channel blockers). The combined action of DvnRV41 and K activators permitted formation of ATP-dependent pores. The combination of DvnRV41 and ATP-dependent pore activator cromakalim inhibited the growth of sensitive strain. The antilisterial activity of structural variants was less important than that of DvnRV41 but their mode of action remained overall similar.
Keywords: Listeria monocytogenes; antibakteriální látky; draslíkové kanály; Bacteriocins; bakteriociny; adenosintrifosfát; rekombinantní proteiny; Adenosine Triphosphate; Microbial Sensitivity Tests; Potassium Channels; Recombinant Proteins; blokátory draslíkových kanálů; Potassium Channel Blockers; Anti-Bacterial Agents; mikrobiální testy citlivosti